2021
DOI: 10.1007/s00122-021-03849-4
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in CsHY2 encoding a phytochromobilin (PΦB) synthase leads to an elongated hypocotyl 1(elh1) phenotype in cucumber (Cucumis sativus L.)

Abstract: Hypocotyl length is a critical determinant in establishing high quality seedlings for successful cucumber production, but knowledge on the molecular regulation of hypocotyl growth in cucumber is very limited. Here we reported identi cation and characterization of a cucumber elongated hypocotyl 1 (elh1) mutant. We found that the longer hypocotyl in elh1 was due to longitudinal growth of hypocotyl cells. With ne mapping, the elh1 locus was delimited to a 20.9-kb region containing three annotated genes; only one … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Similar results were observed in a long hypocotyl mutant of Arabidopsis [ 27 ]. Previous studies have also shown that the hypocotyl elongation rate in the long hypocotyl mutant elh1 was significantly higher than that of the short hypocotyl WT at any time point in cucumber [ 28 ]. Studies of long-hypocotyl mutants, such as lhy7.1 , may provide a theoretical basis for the breeding of long-hypocotyl varieties which could be applied in mechanized production.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar results were observed in a long hypocotyl mutant of Arabidopsis [ 27 ]. Previous studies have also shown that the hypocotyl elongation rate in the long hypocotyl mutant elh1 was significantly higher than that of the short hypocotyl WT at any time point in cucumber [ 28 ]. Studies of long-hypocotyl mutants, such as lhy7.1 , may provide a theoretical basis for the breeding of long-hypocotyl varieties which could be applied in mechanized production.…”
Section: Discussionmentioning
confidence: 99%
“…Cell elongation, rather than cell division, largely contributes to hypocotyl growth [ 29 , 30 ]. Previous studies have shown that hypocotyl growth mainly depends on cell longitudinal elongation in Arabidopsis and cucumber [ 5 , 6 , 28 , 29 ]. We examined the length of the hypocotyl cells of both WT and lhy7.1 grown in an artificial climate box under controlled environmental conditions using semi-thin sections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hypocotyl is an ideal model for studying the response of plant stem to light exposure due to its high sensitivity to light signals (Falcioni et al, 2019;Samimy, 1978;Kato-Noguchi & Kasai, 1991;Mazzella et al, 1997;Boron & Vissenberg, 2014;Hu et al, 2021). Proteomics and metabolomics are effective tools for identifying DEPs, DEMs, and related pathways (Li et al, 2018;Wei et al, 2020;Mirzahosseini et al, 2020;Liu et al, 2019;Fan et al, 2018;Yates et al, 2009;Ryan & Robards, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Kohchi et al (2001) initially reported the long-hypocotyl mutation of the HY2 gene encoding PΦB synthetase in Arabidopsis [10]. Subsequently, abnormal PΦB synthase function was reported in various other species, including the pcd2 mutant in pea (Pisum sativum L.) [11], the se13 mutant in rice (Oryza sativa L.) [12], the elh1 mutant in cucumber (Cucumis sativus L.) [13], the Gmlin1 mutant in soybean [14], and the Mtpφbs mutant in alfalfa (Medicago truncatula) [15]. Studies have shown that chromophore-deficient mutants generally have a light green or yellowish leaf phenotype, accompanied by a reduction in chlorophyll.…”
Section: Introductionmentioning
confidence: 99%